Assessment of platelet activation and function in symptomatic and asymptomatic carotid stenosis, ischaemic stroke and transient ischaemic attack - Kinsella, Justin Andrew (Trinity College (Dublin, Ireland). School of Medicine. Discipline of Clinical Medicine, 2012)
Aims: The purpose of this thesis was to comprehensively assess the levels of platelet activation, platelet function and platelet turnover in patients with moderate or severe asymptomatic or symptomatic carotid artery stenosis, and to perform preliminary experiments to investigate coagulation system potential and endothelial activation in these patients. We performed transcranial Doppler ultrasound to assess for the presence of cerebral microembolic signals (MES), and colour Doppler ultrasound of carotid plaques in these patients. We also performed a pilot study of platelet reactivity using the PFA-100® and VerifyNow® analysers in patients in the convalescent phase following TIA or ischaemic stroke.
Keywords: Neurology, Ph.D.; Ph.D. Trinity College Dublin